SCALE STRUCTURE, AGE AND GROWTH IN THE FRESHWATER CARP, LABEO CALBASU (PISCES/CYPRINIDAE) FROM HARIKE WETLAND, INDIA - Bhatia, N. K.; Dua, A. (Journal of Indian Fisheries Association, 2015)
Age structure and growth profile based on the scale studies of 468 specimens ranging from 17-62 em total length of Labeo calbasu (Hamilton) from Harike wetland (30Â°13’N, 75Â° 12’E), Punjab, India have been described. the present study showed better growth in terms of two important growth parameters namely index of species average size and population weightgrowth intensity. Two distinct phases in its life history have been described that indicates the optimum exploitation of this species from this waterbody. Harvestable size is found to be fish of 34 em total length. The detailed structural elaboration of scale (normal, regenerated, lateral line) has also been done using scanning electron microscopy (SEM). Keywords: Scale, SEM, Age, Growth, Stock Management.